Pertumbuhan dan Serapan Nitrogen Bibit Kelapa Sawit (Elaeis guineensis Jacq.) Pada Fase Main-Nursery Di Beberapa Medium Tumbuh Dengan Efek Sisa Pupuk Organik - Suyuti Dahlan; Armaini '; Wardati ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research aimed to determine the response of the growth of oil palm seedlings and how much nitrogen can reserve by oil palm seedlings on different organic fertilizer sources with some planting medium. This research has done in experimental plantation Agriculture Faculty, University of Riau from October until December 2012. This research used completely randomized factorial design with two treatment factors and three replications. The first factor was source of residue effect of different organic fertilizer include P0: without fertilizer, P1: bird’s manure, P2: Sludge fertilizer, P3: liquid organic fertilizer. The second factor was plant medium as T1: PMK soil, T2: Peat soil, T3: the combination of PMK soil and Peat Soil 50:50. The result showed that the best treatment was of residue effect of liquid organic fertilizer in PMK and Peat soil medium because its can be inclined grow up plant height, stump diameter, amount of leaves, root volume, seedling dry weight and the reserve of nitrogen. Treatment of plant medium was not significant for all parameters. Interaction between the two treatments significantly effect plant height, seedling dry weight and the reserve of nitrogen, but non significantly for amount of leaves, stump diameter and root volume. Key words: Oil Palm, Organic fertilizer, PMK Soil and Peat Soil.